Clinical and epidemiologic characteristics of hospitalized oncological patients with hypercalcemia: a longitudinal, multicenter study - Ropero-Luis, Guillermo; Sanz-Cánovas, Jaime; López-Sampalo, Almudena; Ruiz Cantero, Alberto; Gómez-Huelgas, Ricardo (My University, 2024)
Background There are few studies that have analyzed the characteristics of hypercalcemia in hospitalized oncological patients. Our objectives were to describe the clinical characteristics of hospitalized patients with paraneoplastic hypercalcemia and to identify prognostic variables for mortality. Methods This was an observational, longitudinal, retrospective, and bicentric study. It included adult patients admitted to two hospitals in Málaga, Spain (2014–2018). The minimum follow-up period was 2 years or until death. Results A total of 154 patients were included; the majority (71.4%) were admitted to the internal medicine department. The median follow-up was 3.5 weeks (interquartile range [IQR] 1.1–11.5). The mean (standard deviation) age was 67.6 (12.3) years, with a predominance of males (58.4%). The median (IQR) serum calcium at admission was 13.2 (11.8–14.6) mg/dl. The most common neoplasms were pulmonary (27.3%), hematologic (23.4%), urological (13%), and breast (12.3%). Furthermore, 56.5% of cases had a known history of neoplasia at the time of diagnosis. The parathyroid hormone (PTH) level was determined in 24%; of these, 10.8% had elevated levels. In all, 95.5% of patients died during follow-up. The median survival was 3.4 weeks (95% confidence interval 2.6–4.3). Factors associated with higher mortality were age, serum calcium at admission, previous history of neoplasia, etiology other than multiple myeloma, and noncorrection of hypercalcemia. Conclusions In hospitalized patients, paraneoplastic hypercalcemia was associated with high short-term mortality. Several factors associated with a worse prognosis were identified in these patients.
Keywords: Enfermos de cáncer - Asistencia hospitalaria; Hypercalcemia; Calcium metabolism disorders; Paraneoplastic syndromes; Bisphosphonates; Calcitonin